2020
DOI: 10.1111/pce.13976
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the isomiRome in the vegetative organs of the conifer Pinus pinaster under contrasting water availability

Abstract: An increasing number of microRNAs (miRNAs) and miRNA‐related sequences produced during miRNA biogenesis, comprising the isomiRome, have been recently highlighted in different species as critical mediators of environmental stress responses. Conifers have some of the largest known genomes but an extensive characterization of the isomiRome from any conifer species has been lacking. We provide here a comprehensive overview of the Pinus pinaster isomiRome expressed in roots, stem and needles under well‐watered and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…While diverse sncRNA profiles have been detected in seed tissues, based mostly on available data from angiosperms, there seems to be a general tendency for a higher abundance and diversity of 24-nt sncRNAs regardless of the developmental stage of the seed [16]. In some gymnosperm species, like maritime pine (Pinus pinaster), 24-nt sncRNAs were also highly expressed in embryos when compared to vegetative tissues [3,17] and more abundant in somatic embryos than in zygotic embryos at equivalent stages of development. In Picea glauca, another gymnosperm species, both 21-nt and 24-nt sncRNAs were abundant in embryos [18], this profile being in contrast to that of buds [19], confirming that the 24-nt sncRNAs are mostly present in reproductive tissues.…”
Section: Small Rna Expression Profiles In Embryonic Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…While diverse sncRNA profiles have been detected in seed tissues, based mostly on available data from angiosperms, there seems to be a general tendency for a higher abundance and diversity of 24-nt sncRNAs regardless of the developmental stage of the seed [16]. In some gymnosperm species, like maritime pine (Pinus pinaster), 24-nt sncRNAs were also highly expressed in embryos when compared to vegetative tissues [3,17] and more abundant in somatic embryos than in zygotic embryos at equivalent stages of development. In Picea glauca, another gymnosperm species, both 21-nt and 24-nt sncRNAs were abundant in embryos [18], this profile being in contrast to that of buds [19], confirming that the 24-nt sncRNAs are mostly present in reproductive tissues.…”
Section: Small Rna Expression Profiles In Embryonic Tissuesmentioning
confidence: 99%
“…Small non-coding RNAs (sncRNAs) are usually 20-24 nt long RNA molecules with important regulatory functions during development and environmental responses across all groups of land plants, from bryophytes like Physcomitrella patens [1] and Marchantia polymorpha [2], to the gymnosperms [3] and angiosperms [4]. These small molecules are classified into several classes according to their biogenesis and roles [5], the micro RNAs (miRNAs) being the best characterized group of sncRNAs, and the short-interfering RNAs (siRNAs) the other broad category of plant sncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the miRNA families here detected as differentially expressed after PWN inoculation were also responsive to drought stress in P. pinaster 23 (miR159, miR164, miR166, miR169, miR396, miR529, miR1313, miR3627, miRnovel578), suggesting these families may have a role in the regulation of stress responses in general.…”
Section: Discussionmentioning
confidence: 79%
“…Plant hormone signalling genes were targeted by differentially expressed miRNAs, leading to the suppression of indole acetic acid and zeatin synthesis thus causing the inhibition of plant growth, but the role of the expressed miRNAs in regulating plant immune response was not addressed. In P. pinaster , sRNAs were reported to be involved in the regulation of embryo development 22 and abiotic stress response 23 , but their function in biotic stress has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…In conifers, miRNAs related to somatic embryogenesis have been studied on larch [30], Norway spruce [31], and Picea balfouriana [32]. Stress-related miRNAs were also reported in Sabina chinensis [33] and Pinus pinaster [34]. Unfortunately, the study of lncRNAs on the stress response and somatic embryogenesis has not been reported in conifers at present.…”
Section: Introductionmentioning
confidence: 99%